Respuesta :
7x + 3(x-2) -4x + 8
Using the distributive property, we get:
7x + 3x - 6 - 4x + 8
Using the commutative property, we get
7x + 3x - 4x - 6 + 8
Simplifying, we get:
6x + 2
Using the distributive property, we get:
7x + 3x - 6 - 4x + 8
Using the commutative property, we get
7x + 3x - 4x - 6 + 8
Simplifying, we get:
6x + 2
Distribute.
3x - 6
7x + 3x - 6 - 4x + 8
Now combine like terms
7x + 3x = 10x
10x - 4x = 6x
-6 + 8 = 2
6x + 2
Answer: 6x + 2
3x - 6
7x + 3x - 6 - 4x + 8
Now combine like terms
7x + 3x = 10x
10x - 4x = 6x
-6 + 8 = 2
6x + 2
Answer: 6x + 2